Manajemen Strategi Pada Perusahaan Makanan Anti Food-Waste Berbasis Circular Economy: Studi Kasus Sweetwaste - Rahmat Dwiyanto (GLOBAL SCIENTS PUBLISHER, 2025)
Food waste is a global issue that has a wide impact on the environment and economy. According to the United Nations Environment Programme (2021), around 931 million tons of food are wasted globally each year. In Indonesia, Bappenas recorded that food waste reaches 23–48 million tons per year. In facing this challenge, a business strategy based on the circular economy and sustainability principles is an important key. This study aims to develop a strategic plan for a hypothetical company called SweetWaste, which processes sub-optimal food ingredients into healthy food products with sales value. With a descriptive qualitative approach and using the STP, 4P, SWOT-TOWS, PESTEL, and Ansoff Matrix analysis models, this study formulates a comprehensive strategy to reach young urban consumers who are environmentally conscious. The results of the analysis show that digital education strategies, strengthening local distribution, and diversification of food waste-based products are potential steps to achieve sustainable and competitive growth. These findings provide practical contributions to the development of zero waste food businesses and enrich the literature on strategic management in the context of sustainability.